2015
DOI: 10.1590/1414-462x201500010010
|View full text |Cite
|
Sign up to set email alerts
|

Aposentadorias por invalidez e Doenças Crônicas entre os servidores da Prefeitura Municipal de Uberlândia, Minas Gerais, 1990-2009

Abstract: OBJETIVO: Descrever as causas de aposentadoria por incapacidade permanente entre servidores municipais de Uberlândia, Minas Gerais, e associar com fatores sociodemográficos. MÉTODOS: Foi realizado um levantamento epidemiológico no período de janeiro de 1990 a dezembro de 2009, utilizando dados secundários sobre os servidores da Prefeitura Municipal de Uberlândia. RESULTADOS: Foram avaliadas 403 aposentadorias. Em 46% delas os indivíduos tinham idade inferior a 50 anos. A maioria (96%) se aposentou devido à doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 7 publications
1
7
0
5
Order By: Relevance
“…In the present study, when correlating the morbidities present in these individuals at the beginning of follow-up, the authors concluded that diseases of the musculoskeletal system and MBD constitute strong predictors for early retirement (29) . It is emphasized that the aggravations that led to definitive retirement, that is, in the disability pensions in the present study, are similar to those found in another Brazilian investigation (16) , in which MBD was the first cause (22.6% ), second was MSD (14.8%), CAD the third cause (13.8%) and cancer the fourth cause (11.9%). The latter finding was different from the present study, in cancer ranked in fifth place.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the present study, when correlating the morbidities present in these individuals at the beginning of follow-up, the authors concluded that diseases of the musculoskeletal system and MBD constitute strong predictors for early retirement (29) . It is emphasized that the aggravations that led to definitive retirement, that is, in the disability pensions in the present study, are similar to those found in another Brazilian investigation (16) , in which MBD was the first cause (22.6% ), second was MSD (14.8%), CAD the third cause (13.8%) and cancer the fourth cause (11.9%). The latter finding was different from the present study, in cancer ranked in fifth place.…”
Section: Discussionsupporting
confidence: 89%
“…These results were also identified in national and international surveys that indicate that they are related to the double day that most women experience, that is, work activities plus domestic activities. This increases their overload, stress and health problems, by the consequent reduction in time for leisure and health care, especially for promotion and prevention (15)(16)(17)(18)(19)(20) . Regarding the marital status variable, most of the studies are performed with secondary data from the social security systems, in which this variable is often not registered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations